(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
The main objective of this study was to identify the prophages and antimicrobial resistance profile of Bacillus subtilis using computational methods. Prophages are potential therapeutic antimicrobial agents against antibiotic- resistant pathogens. The potential of prophage to induce antimicrobial resistance and increase pathogenicity in bacterial genomes resulted in renewed interest in the identification of prophage sequences and their associated antimicrobial resistant genes in bacterial genomes. Sequences of Bacillus subtilis retrieved from the sequence raw archive (SRA) of the National Centre for Biotechnology Information was submitted to bacterial viral bioinformatics resource centre for genome assembly. Prophage sequences were identified using the PHASTER server. The region length, region position and GC percentage of nucleotides of prophage sequences were identified. The antimicrobial resistance gene family, drug class, resistance mechanism and length of reference sequences were identified using the resistance gene identifier protocol of the comprehensive antimicrobial resistance database. It can be concluded that the Bacillus subtilis strain evaluated contained prophage sequences associated with antimicrobial resistance genes, there is, therefore, the need to assess the safety of bacteriophages before they are utilized as alternative to antibiotics.